Mitogen-activating protein kinase kinase kinase kinase-3, inhibited by Astragaloside IV through H3 lysine 4 monomethylation, promotes the progression of diabetic nephropathy by inducing apoptosis. Issue 5 (2nd May 2022) - Fan, Yuyan; Fan, Hongyu; Li, Ping; Liu, Qingshan; Huang, Lixia; Zhou, Yilun
ABSTRACT: Astragaloside IV (AS-IV) is a bioactive saponin extracted from the Astragalus root and has been reported to exert a protective effect on diabetic nephropathy (DN). However, the underlying mechanism remains unclear. Herein, we found that AS-IV treatment alleviated DN symptoms in DN mice accompanied by reduced metabolic parameters (body weight, urine microalbumin and creatinine, creatinine clearance, and serum urea nitrogen and creatinine), pathological changes, and apoptosis. Epigenetic histone modifications are closely related to diabetes and its complications, including H3 lysine 4 monomethylation (H3K4me1, a promoter of gene transcription). A ChIP-seq assay was conducted to identify the genes regulated by H3K4me1 in DN mice after AS-IV treatment and followed by a Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis. The results showed that there were 16 common genes targeted by H3K4me1 in normal and AS-IV-treated DN mice, 1148 genes were targeted by H3K4me1 only in DN mice. From the 1148 genes, we screened mitogen-activating protein kinase kinase kinase kinase-3 (MAP4K3) for the verification of gene expression and functional study. The results showed that MAP4K3 was significantly increased in DN mice and high glucose (HG)-treated NRK-52E cells, which was reversed by AS-IV. MAP4K3 silencing reduced the apoptosis of NRK-52E cells under HG condition, as evidenced by decreased cleaved caspase 3 and Bax (pro-apoptotic factors), and increased Bcl-2 and Bcl-xl (anti-apoptotic factors). Collectively, AS-IV may downregulate MAP4K3 expression by regulating H3K4me1 binding and further reducing apoptosis, which may be one of the potential mechanisms that AS-IV plays a protective effect on DN. GRAPHICAL ABSTRACT: uf0001